[The mathematics department and the mathematics and statistics computing laboratory hold the lecture series] - Mathematics Department, De La Sall Uiversity, Manila (Animo Repository, 1997)
The Mathematics Department and the Mathematics and Statistics Computing Laboratory hold the 4th DLSU lecture series to discuss the perspectives, problems, and practices in mathematics.